2016
DOI: 10.1186/s12894-016-0187-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk for urological cancer associated with anxiety disorder: a retrospective cohort study

Abstract: BackgroundAnxiety disorders (ADs) are common with a high rate of medical comorbidities. Although the association between ADs and the overall cancer risk remains controversial, patients with ADs were found to be more likely to develop specific cancer types. Herein, we estimated the risk of developing urological cancers among patients with ADs in a 5-year follow-up period using a population-based database.MethodsTwo study cohorts were identified from the Taiwan Longitudinal Health Insurance Database 2005: patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In a recent study of perceived stress at work and developing all cancers, a stressful job was weakly associated with an increased risk of developing bladder cancer among others (OR ¼ 1.37, 95% CI: 1.03-1.81) [36]. Similarly, Chen et al [37] have found a weak association between anxiety disorders and the development of bladder cancer (hazard ratio ¼ 2.94, 95% CI: 1.89-4.58), whereas Gu et al [38] found a weak association between less than 7-8 h sleep duration and bladder cancer (hazard ratio ¼ 1.10, 95% CI: 1.00-1.20).…”
Section: Lifestylementioning
confidence: 85%
“…In a recent study of perceived stress at work and developing all cancers, a stressful job was weakly associated with an increased risk of developing bladder cancer among others (OR ¼ 1.37, 95% CI: 1.03-1.81) [36]. Similarly, Chen et al [37] have found a weak association between anxiety disorders and the development of bladder cancer (hazard ratio ¼ 2.94, 95% CI: 1.89-4.58), whereas Gu et al [38] found a weak association between less than 7-8 h sleep duration and bladder cancer (hazard ratio ¼ 1.10, 95% CI: 1.00-1.20).…”
Section: Lifestylementioning
confidence: 85%